Anatomical landmarks accurately determine interfractional lymph node shifts during radiotherapy of lung cancer patients. Issue 1 (July 2015) - Hoffmann, Lone; Holt, Marianne Ingerslev; Knap, Marianne Marquard; Khalil, Azza Ahmed; Møller, Ditte Sloth
Abstract Background and purpose Low contrast in the cone-beam computed tomography (CBCT) scans hampers fast online evaluation of interfractional changes in the lymph node position on a daily basis. In this study we have investigated whether high-contrast anatomical landmarks in the vicinity of the nodes may be used as surrogates for the lymph node positions. Materials and methods Forty lung cancer patients were treated with an online CBCT-based setup strategy involving soft-tissue match on the primary tumor. One hundred and sixteen lymph nodes were delineated separately on the planning-CT scans and categorized according to the lymph node stations. Five anatomical landmarks were selected as surrogate structures and assigned to the individual nodes. In addition, the carina was delineated. Registrations between the planning-CT and the daily CBCTs were performed retrospectively and positional deviations between the nodes and the surrogate structures or the carina were registered. Results The mean displacement between lymph nodes and surrogate structures was 1.6 mm with systematic/random errors of 0.7/0.7 mm, significantly smaller than the mean displacement between nodes and the carina. Conclusions The position of the lymph nodes can be evaluated using selected anatomical landmarks on a daily basis using CBCT.